Biomechanical evaluation of two miniplate fixations applied in the anterior region after Le Fort I osteotomy: an experimental study - DOLANMAZ, DOĞAN; Esen A.; Celik B.; DOLANMAZ D. (My University, 2022)
© 2021 The British Association of Oral and Maxillofacial SurgeonsThe aim of this experimental study was to evaluate the reliability of two-plate fixations applied to the anterior region of the maxilla after Le Fort I osteotomy in terms of stability. Twenty polyurethane-based skull models were used to evaluate two fixation techniques. Two groups consisting of four and two L-shaped titanium miniplates were tested. Each group was tested with the application of vertical forces in the anteroposterior direction using a servohydraulic testing unit. The displacement values in each group at each stage (from 10 N - 120 N) were compared using the Mann-Whitney U test. The displacement values for the two groups were not statistically significant up to 20 N, but differed significantly between 20 N and 120 N (p < 0.05). The results showed that the biomechanical behaviour of fixation with four miniplates was better than that of two after a load of 20 N. It can be concluded that when the amount of maxillary advancement is increased to 10 mm or more, fixation with only two plates does not provide sufficient stability experimentally.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Diş Hekimliği; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Otolaryngology; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; KULAK BURUN BOĞAZ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; DENTISTRY, ORAL SURGERY & MEDICINE; OTORHINOLARYNGOLOGY; Cerrahi; Ağız Cerrahisi; Surgery; Oral Surgery; Otorhinolaryngology; Le Fort I osteotomy; maxillary advancement; stability